Metaphorical expressions in the book Ngawur Karena Benar by Sujiwo Tejo: A pragmatic approach - Hakim, M. Arif Rahman; Medina, Sabila (Journal on English as a Foreign Language (JEFL), 2017)
This study concerns on metaphorical expressions in the book Ngawur Karena Benar written by Sujiwo Tejo and their nonliteral meaning. In finding the metaphorical expressions, researchers used the theory of metaphor. Otherwise, in analyzing the nonliteral meaning, it was used relevance approach. According to relevance theory, the process of interpreting a metaphorical expression comprises the following steps: decoding the linguistic input by arraying possible meanings of an utterance and drawing inferences by taking into account both the results of linguistic decoding. The problems are to answer: 1) what metaphorical expressions can be found in the book Ngawur Karena Benar by Sujiwo Tejo, 2) what are the meanings of the metaphorical expressions used in the book. This study applied qualitative research method by employing document analysis approach to get detailed data description from the object analysis. Results of this study revealed that the metaphorical expressions are used to deliver a complicated circumstance in revealing the real condition. In line with the finding, the nonliteral meaning of the metaphorical expression needs an intralinguistic that is the information we can receive by decoding the linguistic input while the extralinguistic factor is the assumptions taken from context by drawing inferences.